2018
DOI: 10.1002/ejoc.201801612
|View full text |Cite
|
Sign up to set email alerts
|

A New Amphiphilic Brønsted Acid as Catalyst for the Friedel–Crafts Reactions of Indoles in Water

Abstract: A new amphiphile 1a featuring with two ‐NHSO2C4F9 sites is designed and synthesized as Brønsted diacid. The amphiphilicity arose from nano‐aggregations of hydrophobic fluorocarbon chains and extension of hydrophilic NH groups, confirmed by Tyndall effect and TEM. The acidity of 1a rivals to concentrated H2SO4, examined by the Hammett acidity function, 31P NMR and conductance titration. Compound 1a demonstrated excellent catalytic performance in the Friedel–Crafts alkylation of indoles in water. Reactive substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The red laser beam becomes invisible in deionized water without such particles (Figure 1B, middle). Some researchers have used TE to qualitatively evaluate nanolevel aggregation 30 or formation of colloidal catalysts. 31 However, the analytical advantages of the TE are far from being fully explored.…”
mentioning
confidence: 99%
“…The red laser beam becomes invisible in deionized water without such particles (Figure 1B, middle). Some researchers have used TE to qualitatively evaluate nanolevel aggregation 30 or formation of colloidal catalysts. 31 However, the analytical advantages of the TE are far from being fully explored.…”
mentioning
confidence: 99%
“…The solubility control in the organic reactions can be implemented by the addition of water. Recently, many efforts have been devoted to the development of aqueous catalytic reactions from the perspective of green chemistry ,. However, the product purification via chromatography or recrystallization is still unavoidably solvent‐ and time‐consuming.…”
Section: Figurementioning
confidence: 88%
“…As a proof of concept, Michael addition reaction of indole ( 1 a ) with pent‐1‐en‐3‐one ( 2 a ) was carried out in water to construct 3‐substituted indoles, a type of important precursors in the synthesis of biologically active compounds and natural products ,, . However, the reaction was sluggish based on TLC analysis.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Named after the physicist John Tyndall, TE is a type of light scattering that takes place when visible light is passed through a colloidal solution with a particle size distribution that lies in the 400 to 750 nm range 21 . This phenomenon has already been used as a visual screening method to detect microprecipitates in blends of parental drug solutions 22,23 as well as to evaluate nanolevel aggregation and characterise colloidal catalyst and functional materials [24][25][26][27] . More recently, Xiao et al 28 added quantitative character to a TE-based colorimetry approach and demonstrated a ca.…”
Section: Introductionmentioning
confidence: 99%